2021
DOI: 10.7759/cureus.16816
|View full text |Cite
|
Sign up to set email alerts
|

Major Bleeding Complications in COVID-19 Patients

Abstract: Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection has been associated with thrombotic phenomena in the early stages of the disease, but also, less frequently, with major bleeding between the second and third week after onset, particularly in patients treated with therapeutic anticoagulation. This article describes four cases of patients admitted to the hospital with severe SARS-CoV-2 pneumonia who had arterial bleeding as a complication while on low-molecular-weight heparin at therapeutic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 11 publications
2
20
0
Order By: Relevance
“…Current evidence shows that bleeding in patients with severe COVID-19 pneumonia is not only due to anticoagulation treatment, but also due to microvascular damage. 9 In line with our findings, some previous reports showed major bleeding events in critically ill patients with COVID-19 which ranged between 4.8% and 18%. 10,11 In comparison to recent reports, 12,13 current study showed a lower prevalence of thrombotic events.…”
Section: Discussionsupporting
confidence: 92%
“…Current evidence shows that bleeding in patients with severe COVID-19 pneumonia is not only due to anticoagulation treatment, but also due to microvascular damage. 9 In line with our findings, some previous reports showed major bleeding events in critically ill patients with COVID-19 which ranged between 4.8% and 18%. 10,11 In comparison to recent reports, 12,13 current study showed a lower prevalence of thrombotic events.…”
Section: Discussionsupporting
confidence: 92%
“…While thrombotic events usually occur in the first week of acute infection, after 10th day of COVID-19, tendency for bleeding mechanisms begins to outweigh. 13 This case, unusually, presented with hematoma, just after the symptoms began. The unusual situation of tendency for bleeding at the beginning of the infection does not overlap with current knowledge and philosophy of clotting mechanisms behind COVID-19.…”
Section: Discussionmentioning
confidence: 87%
“…Nevertheless, the main symptom was abdominal pain, and bleeding into the muscles should always be taken into account when diagnosing COVID-19 patients with abdominal pain. In the literature review, we found two reports of bleeding events in the abdominal muscles in a patient in the course of COVID-19 upon anticoagulant treatment [ 15 , 16 ].…”
Section: Discussionmentioning
confidence: 99%